Manipulation of the ATP pool as a tool for metabolic engineering. (27th November 2015) - Hädicke, Oliver; Klamt, Steffen
Abstract : Cofactor engineering has been long identified as a valuable tool for metabolic engineering. Besides interventions targeting the pools of redox cofactors, many studies addressed the adenosine pools of microorganisms. In this mini-review, we discuss interventions that manipulate the availability of ATP with a special focus on ATP wasting strategies. We discuss the importance to fine-tune the ATP yield along a production pathway to balance process performance parameters like product yield and volumetric productivity.